Serum cytokine levels, and anxiety and depression rates in patients with alopecia areata - Ataseven, A.; Saral, Y.; Godekmerdan, A. (Wiley-Blackwell, 2011)
[Abstract Not Available]
30th Congress of the European-Academy-of-Allergy-and-Clinical-Immunology (EAACI) -- JUN 11-15, 2011 -- Istanbul, TURKEY